Designing and study of composites reinforced with shredded corn stalks using a variety of matrices based on dammar, epoxy and acrylic resins - Cosmin Mihai Mirițoiu; Dan Dobrotă; Daniela Popa (Polymer Testing)
The primary goal of this research was to develop and evaluate environmentally friendly composite materials. Shredded corn stalks, regarded as both renewable resources and industrial by-products, were employed as the main reinforcement. Several synthetic resins were used as matrices, including one epoxy resin and two types of acrylic resins, as well as hybrid resins incorporating natural Dammar resin as a significant component. A range of composites was manufactured and tested for properties such as tensile, compressive, and flexural strength, vibration resistance, Shore D hardness, and water absorption. Under the tensile test, the samples reinforced only with shredded corn stalks exhibited strength values below 7 MPa and elongation at break below 2.5 %. From the perspective of compressive strength, values ranging between 9 and 23.5 MPa were obtained, exceeding the tensile strength values. In fact, the tensile strength is 3–3.6 times lower compared to the compressive strength (by comparing materials of the same type). For the samples reinforced only with shredded corn stalks, the flexural strength was the lowest, with values ranging between 0.98 and 3 MPa. When comparing compressive and flexural strengths, it is observed that the compressive strength is 7.8–9.2 times higher. To increase the tensile and flexural strengths, facets made of a mixed fiber composition of 70 % silk and 30 % linen were applied. Following the addition of facets composed of 70 % silk and 30 % linen, tensile strength increased by 9.5–13.3 times, and flexural strength increased by 8.7–17.8 times. Furthermore, a greater proportion of natural Dammar r. esin improved the ductility of the composites but resulted in a decrease in overall strength. As a practical application of the study, a shelf and a cupboard door were constructed from the developed materials. The research ultimately emphasizes the promising mechanical properties of these composites, indicating their potential for use in the furniture industry, particularly in the production of chipboard.